PELAKSANAAN PROMOSI OBJEK WISATA PUNCAK KOMPE KOTO MESJID KABUPATEN KAMPAR - Hutagalung, Tiurma Alfarida; ,, Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Promotion plays a crucial role in developing tourism destinations as it directly influences public awareness and the image of a tourist attraction. This study examines the implementation of promotional activities at Puncak Kompe Tourist Attraction, located in Koto Mesjid Village, Kampar Regency, Riau Province. Puncak Kompe is known for its natural beauty, offering panoramic views of hills and lakes that resemble the charm of Raja Ampat. This research employs a descriptive qualitative method with data collected through observation, interviews, and documentation involving the management team, photographers, and visitors. The results indicate that promotional activities at Puncak Kompe remain simple and not yet optimally organized. he main obstacles identified include a lack of government support, insufficient professional staff in tourism promotion, and the absence of a long-term promotional plan. To address these challenges, the management has reactivated social media accounts, strengthened collaborations with communities and local government, and developed more creative and engaging promotional content. This study is expected to serve as an evaluation and reference for tourism managers and local authorities in enhancing effective and sustainable promotion efforts so that Puncak Kompe can continue to grow as one of the leading tourist destinations in Kampar Regency. Keyword: Promotion Implementation, Puncak Kompe, Koto Mesjid Village, Nature Tourism, Promotion Obstacle.